Status of Lipid Profile among the Hypertensive Patients in Bangladesh - Reza, CM; Kabir, ASMA; Biswas, Tuhin; Choudhury, Kamrun Nahar; Rahman, Md Zahidur; Hussain, Deen AS; Ghosh, Shantonu Kumar (University Heart Journal, 2014)
Back ground: Hypertension and dyslipidemia are associated with oxidative stress and are major causes of cardiovascular disease amounting to 30% of global death rate. It is widely accepted that cardiovascular disease is associated with hypertension and increased blood levels of low-density lipoprotein (LDL), total cholesterol (TC), and triglycerides. In contrast, a low level of high density lipoprotein (HDL) is a risk factor for mortality from cardiovascular disease. Hypertension is a major public health problem in developed and developing countries. Methods: This study was a cross sectional study in which 159 diagnosed hypertensive patient and 75 with normal blood pressure (normotensive) were enrolled. These patients sought a through health cheek up including blood pressure assessment between May 2012 to April 2013 in Tairunnessa Memorial Medical College and Hospital. Lipid parameter total cholesterol (TC), triglyceride (TG), low density lipoprotein ( LDLc) and high density lipoprotein (HDLc) were estimated by enzymatic colorimetric test. Results: The mean of Systolic blood pressure and Diastolic blood pressure of hypertensive were higher than normotensive (p<0.001). The serum levels of total cholesterol, triglyceride and LDL-C in hypertensive subject were higher than normotensive and statistically significant (p<0.001). Serum HDL-C was significantly lower (p<0.001) in hypertensive patients than in normotensive. Conclusion: Analytical results of the study revealed that hypertensive patients have been found to have close association with dyslipidemia. Hypertension and dyslipidemia can be modified either by proper life style changes or medical management or by the combination of the both. This study suggests that hypertensive patients need measurement of blood pressure and lipid profile at regular interval to prevent heart diseases and stroke. DOI: http://dx.doi.org/10.3329/uhj.v9i1.19505 University Heart Journal Vol. 9, No. 1, January 2013; 13-17